PEMBENTUKAN KARAKTER CINTA RASUL PADA PEMUDA JAMAAH MAJELIS TA’LIM WAL MAULID ARRIDWAN MALANG - Ahmad NailuMinhajjil Qowim; Fathurrahman Alfa; Moh Eko Nasrullah (VICRATINA, 2020)
The presence of Majelis Ta,lim Wal Maulid in the middle of community is another alternative which has a great impact in relation to build a characters which so far may only involve formal education institution. Through assembly like this, many innovations and creations have been produced in terms of dakwah methods that can attract the attention of the public to join. Based on Islamic teachings in preaching must be with kindness, patience, and other good ways. The existence of such an assembly is a favorite for Muslims in certain areas. Beside of being a fun siar, Majelis ta’lim Wal Maulid becomes the right place to explore Islamic religious knowledge. The organization also has a special role in building human character to become a good person. This assembly introduces the personality of the Prophet Muhammad gradually to be able to foster a sense of love for him, so the evidence of knowledge and love of the Prophet is to apply everything that has been exemplified in daily life and there will be no more words or behavior that show the bad character of humans. The focus of the research is the patterns and efforts made in the process of forming the character of loving the Prophet Muhammad by using qualitative research descriptive. The process of collecting data uses observation, interviews, and documentation.